(untitled) (Scientific journal of the Fergana State University, 2025)
This article analyzed the formation of the pension system, the procedure for paying pensions to the families of military servicemen and war disabled people during the war years, and the benefits given to them in this regard. Also, the bureaucratic situations in the appointment of pensions, non-granting of pensions to citizens who have the right to receive benefits established by law, and cases of non-appointment of pensions and benefits on time have been reflected.